Novel exomic rare variants associated with venous thrombosis. (30th March 2020) - Deguchi, Hiroshi; Shukla, Meenal; Hayat, Mohammed; Torkamani, Ali; Elias, Darlene J.; Griffin, John H.
Summary: Exomic rare variant polymorphisms ( c . 300 000) were analysed in the Scripps Venous Thrombosis (VTE) registry (subjects aged <55 years). Besides coagulation factor V ( F5 ) single nucleotide polymorphisms (SNPs), family with sequence similarity 134, member B ( FAM134B; rs78314670, Arg127Cys) and myosin heavy chain 8 ( MYH8 ; rs111567318, Glu1838Ala) SNPs were associated with recurrent VTE ( n  = 34 cases) (false discovery rate‐adjusted P  < 0·05). FAM134B (rs78314670) was associated with low plasma levels of anticoagulant glucosylceramide. Analysis of 50 chr17p13.1 MYH rare SNPs (clustered skeletal myosin heavy chain genes) using collapsing methods was associated with recurrent VTE ( P  = 2·70 ×10 −16 ). When intravenously injected, skeletal muscle myosin was pro‐coagulant in a haemophilia mouse tail bleeding model. Thus, FAM134B and MYH genetic variants are plausibly linked to VTE risk.